Can Superabsorbent Polymers Improve Plants Production in Arid Regions? - Mohsen Jahan; Mehdi Nassiri Mahallati (Advances in Polymer Technology)
Superabsorbent polymers (SAPs) have shown to be quite effective and useful in acting as a reservoir for water and some nutrients in arid and semiarid regions. There are many studies in Iran that have been performed in relation to SAPs and their useful application in agriculture; however, there is still a lack of its applied definition in arid regions. Therefore, this study was conducted with the aim of doing a meta-analysis of the results of studies conducted in Iran and answering a general question about whether the application of SAPs has been effective in enhancing the production or not, and if so, how much of SAP is recommended. To conduct this research, articles published during 2006–2016 on the subject of the effects of different rates of SAP application on yield and yield components of crops (including cereals, legumes, and medicinal and grassland plants) were investigated. The results of the meta-analysis showed that the mean consumption rate of SAPs for cereals, legumes, and medicinal and grassland plants was 83, 322, 1031, and 210 kg ha−1, respectively, and that, at these SAP application rates, the mean seed yield in cereals, medicinal plants, and legumes increased by 15.2, 12.6, and 38% (equivalent to 1059, 345, and 452 kg ha−1), respectively, compared with the control. Dry matter response to superabsorbent application was slower compared with the seed yield response. The mean consumption of 83 kg ha−1 of superabsorbent for cereals increased seed yield by 15.2% on average. According to the results, it seems that the application of 100 kg SAP ha−1 is the most appropriate rate for increasing seed and dry matter yields and satisfying economic aspects. These study findings may shed light on the environment and socioeconomic concerns and improve efficacy and reduction of costs.